2008
DOI: 10.1007/s00436-008-1273-0
|View full text |Cite
|
Sign up to set email alerts
|

New bedding site examination-based method to analyse deer ked (Lipoptena cervi) infection in cervids

Abstract: Invasion of the deer ked (Lipoptena cervi), an ectoparasitic fly commonly found in cervids, has been rapid in Finland during the last four decades. As the distribution area of this species has expanded from the south towards the northern latitudes, the associated problems have become more evident. Various animals such as horses, cattle and especially reindeer have been reported to host this parasite. Moreover, in certain areas, the deer ked causes major inconveniences for humans potentially limiting recreation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 17 publications
0
45
0
Order By: Relevance
“…Besides the ticks from Ixodes ricinus L., 1758 complex, deer keds (Lipoptena cervi L., 1758) are considered as one of the most frequently occurring blood-sucking ectoparasites of cervids in Europe (Haigh et al 2002;Kaunisto et al 2009). After the mating, inside the uterine sac of adult female fly, larva develops and when is ready to pupate, it is extruded out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the ticks from Ixodes ricinus L., 1758 complex, deer keds (Lipoptena cervi L., 1758) are considered as one of the most frequently occurring blood-sucking ectoparasites of cervids in Europe (Haigh et al 2002;Kaunisto et al 2009). After the mating, inside the uterine sac of adult female fly, larva develops and when is ready to pupate, it is extruded out.…”
Section: Introductionmentioning
confidence: 99%
“…Bartonella sp., Borrelia sp., Trypanosoma (Megatrypanum) sp. as well as some filarial nematodes are transmitted by Hippoboscidse (Nelson & Bainborough 1963;Böse & Petersen 1991;Dehio et al 2004;Lane et al 2005;Reeves et al 2006;Kaunisto et al 2009). Bacterial aggregates of Bartonella schoenbuchensis have been observed in the Explanations: Maximum number of deer keds per sample of skin was three individuals; minimum number was one deer ked per sample; prevalence of infestation of deer could not be calculated as deer keds were removed from samples of skin not from the whole body of individual deer.…”
Section: Introductionmentioning
confidence: 99%
“…The known Central European breeding hosts (sensu Bequaert 1953) that support reproduction of L. cervi are the red deer (Cervus elaphus), the roe deer (Capreolus capreolus), and, to a lesser extent, the fallow deer (Dama dama;Haarløv 1964). In Fennoscandia, the main host is the moose (Alces alces; Hackman et al 1983;Andersson 1985), but a few records of successful reproduction have been reported on the reindeer (Rangifer tarandus) as well (Kaunisto et al 2008). The white-tailed deer (Odocoileus virginianus) is also among the breeding hosts of L. cervi in North America, but the prevalence of infection seems relatively low (Matsumoto et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Texture of the snow during this experiment was ideal because it resembled snow density on bedding sites of the endothermic hosts. Pupae of L. cervi are most commonly found on the bedding sites of cervids, and when the resting large-bodied cervids melt the snow underneath, the upper snow layer of the bedding site thus becoming very dense (Kaunisto et al 2009). In our experiment, pupae were mostly exposed to below zero temperatures.…”
Section: Discussionmentioning
confidence: 99%